DISCOURSE AND HISTORY IN THE MEDIA: WAYS OF ENUNCIATING THE QUILOMBOLA SUBJECT IN VIDEOS ON YOUTUBE - Souza, Claudemir [UNESP] (Centro Univ Uniabeu, 2020)
This article aims to analyze the way of enunciating the quilombola subject in two videos of different discursive genres hosted on the YouTube digital platform, namely: the film Quilombo, directed by Caca Diegues, from 1984, and the documentary Quilombos do seculo XXI, of the TV Justica, from 2019. The analysis of these statements, which constitute a corpus to which other materialities will be related, will follow the theoretical-analytical principles of the foucaultians discursive studies, based on Michel Foucault's proposal of an archeogenealogical discourse analysis. With this, we hope to contribute with the insertion of the theme Afro-Brazilian History and Culture in language teaching, discussing linguistic-discursive phenomena that are linked to historical, social and culturais practices of the present time. We conclude that, in the analyzed statements, the quilombola subject is discursivized by the other in a narrative that refers to the Quilombo de Palmares, because of its historical importance, and is authorized to discuss contemporary issues about prejudice, citizenship and the rights that prefigure it.
Keywords: Discourse analysis; YouTube; Quilombola subject